Pedagang Pasar Bringin: Faktor-faktor yang mempengaruhi keputusan penggunaan produk Bank Syariah - Fauzizah, Nurul; Setiawan , Ari (Journal of Halal Industry Studies, 2023)
This research is inspired by which Pasar Bringin as the center of the economy as many  many traders are no aware to the prductt of Syarah Bank. This is due to public knowledge about Islamic banks is still poor and the social environment is less supportive. People still use traveling bank as capital loan in the market. The sample in this study were traders in Pasar Bringin in 93 respondents. The results show that: Knowledge has a positive and significant effect on the decisions of market traders in using Islamic Bank products, Social environment has a positive and significant effect on the decisions of market traders in using Islamic Bank products, Religiosity has a positive and significant effect on market traders' decisions in using Islamic Bank products. In general, interest is able to mediate the influence of knowledge, social environment, and religiosity on the decisions of market traders in using Islamic Bank products.